Strong precursor softening in cubic CaSiO 3 perovskite - Chi Zhang; Jin-Yuan Yang; Tao Sun; Huai Zhang; John P. Brodholt (Proceedings of the National Academy of Sciences, 2025)
CaSiO 3 perovskite (CaPv) is the last major mineral in the Earth’s lower mantle whose elasticity remains largely unresolved. Here, we investigate the elasticity of CaPv using ab initio machine-learning force fields (MLFF). At room temperature, the elasticity of tetragonal CaPv determined by MLFF molecular dynamics (MD) agrees well with experimental measurements after considering temperature induced variations in the hydrostatic structure, proving the effectiveness of the method. We use the MLFF MD in the NPT ensemble to establish the tetragonal–cubic phase boundary and confirm that in the lower mantle CaPv is in the cubic phase. The elasticity of cubic CaPv shows distinct temperature dependence at different ranges: it is linear at high temperatures, whereas it exhibits anomalous precursor softening near the tetragonal–cubic phase boundary. The temperature interval of precursor softening widens as the pressure increases and overlaps with the temperature profile of subducted cold slabs near the core–mantle boundary. While cubic CaPv is seismically invisible along the average mantle geotherm, it may induce low-velocity zones with negative temperature anomaly, leading to the view that the large low shear velocity provinces (LLSVPs) may be caused by subducted oceanic crust rich in CaPv with temperature lower than ambient mantle. A cool, rigid LLSVP may help explain the preferential formation of mantle plumes at its margins, as well as its weaker seismic anisotropy.